Effects of Boron, Zinc, and Iron on the Gentiopicroside Content and Yield of Gentian - YU, Cai-Lian; LUO, Sheng-Guo; PENG, Xian-Long; LIU, Yuan-Ying (Pedosphere, 2006)
A field experiment of 2-year-old gentian （Gentiana manshurica Kitag.） with application of boron （B）, zinc （Zn）, and iron （Fe） in Taikang County, Heilongjiang Province, was conducted to study the effects of the three microelements on gentiopicroside content in the roots of gentian, uptake of these elements, and root dry weight as well as the ratio of root dry weight to fresh weight. Zinc sulfate, ferrous sulfate, and borax were split sprinkled on 2-year-old gentian on June 26, July 18, and August 25, 2002, with sprinkling water taken as a control. Compared with the control, applying B significantly increased （P 〈 0.05） the gentiopicroside content by 7.9%, and there was a highly significant increase of 22.4% （P 〈 0.01） in the root dry weight. Meanwhile, B content in the shoots of gentian gradually increased from the vegetative to the harvesting period, while Fe decreased at first and then increased. Fc treatment increased the gentiopicroside content only by 4.0% and the content was slightly decreased by the Zn treatment （3.1%） as compared to the control. The three microelements had different effects on the gentiopicroside content and appropriate microelement application could increase active ingredient content of gentian.